2019
DOI: 10.1016/j.tmaid.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of respiratory viruses and presence of respiratory symptoms in French pilgrims during the 2016 Hajj: A prospective cohort study

Abstract: Medical follow-up and systematic nasal swabbing were performed pre-and post-Hajj. Additional samples were obtained per-Hajj, at symptom onset in ill pilgrims. Viruses were identified using the BioFire FilmArray ® Respiratory multiplex qualitative PCR panel. Results: 109 pilgrims were included. 83.5% presented respiratory symptoms during Hajj and 39.5% were still symptomatic on return. 5.5% of pre-Hajj, 95.2% of per-Hajj (at symptom onset) and 46.5% of post-Hajj samples tested positive (p < 0.0001). Acquisition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 34 publications
(62 reference statements)
6
18
0
Order By: Relevance
“…It is likely that the living conditions in Mina encampment in relative promiscuity and sharing of cooking, food, hygiene and sanitary facilities are responsible for the high rate of environmental contamination by respiratory pathogens from ill pilgrims with possible subsequent transmission to pilgrims through contact with fomites. Although most pilgrims have onset of respiratory symptoms shortly after their arrival in Saudi Arabia (likely resulting from inter-human transmission of respiratory pathogens in various crowed infrastructures in the city), we observed a bimodal pattern of clinical respiratory symptoms with a lower secondary peak occurring in Mina [24]. Our results suggest that the source of contamination for respiratory pathogens might differ in Mecca and Mina, with a possible additional role for contaminated fomites in Mina, besides air-transmission.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…It is likely that the living conditions in Mina encampment in relative promiscuity and sharing of cooking, food, hygiene and sanitary facilities are responsible for the high rate of environmental contamination by respiratory pathogens from ill pilgrims with possible subsequent transmission to pilgrims through contact with fomites. Although most pilgrims have onset of respiratory symptoms shortly after their arrival in Saudi Arabia (likely resulting from inter-human transmission of respiratory pathogens in various crowed infrastructures in the city), we observed a bimodal pattern of clinical respiratory symptoms with a lower secondary peak occurring in Mina [24]. Our results suggest that the source of contamination for respiratory pathogens might differ in Mecca and Mina, with a possible additional role for contaminated fomites in Mina, besides air-transmission.…”
Section: Discussionmentioning
confidence: 58%
“…Hotel bathroom and ablution area equipments in Mecca were also highly contaminated. Among the French pilgrims surveyed in 2016 [15] and 2018 (unpublished data) who have stayed in the places investigated in the present survey, 16.3% acquired coronaviruses, 16.4% S. aureus, 17.3% K. pneumoniae, 25.5% S. pneumoniae, 26.7% HRV and 30.3% acquired H. influenzae during their stay in Saudi Arabia (Fig. 2).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In a systematic review of 31 studies, Al-Tawfiq et al showed that human rhinovirus (HRV) and influenza viruses were the most common viral respiratory pathogens isolated from ill Hajj pilgrims [6]. In addition, human non-MERS coronaviruses (HCoV) were also a common cause of RTIs during the event [7]. On the other hand, Streptococcus pneumoniae, Haemophilus influenzae and Staphylococcus aureus were shown to be the most commonly acquired respiratory bacteria at the Hajj [5].…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of polymicrobial interactions in the nasopharynx among Hajj pilgrims is important for many reasons. Carriage of more than one pathogen is common among Hajj pilgrims, whether or not they present with respiratory symptoms [7]. Colonization is the initial step in the disease process [11].…”
Section: Introductionmentioning
confidence: 99%